Blood exposure to graphene oxide may cause anaphylactic death in non-human primates. (December 2020) - Lin, Yunfeng; Zhang, Yu; Li, Jiang; Kong, Huating; Yan, Qinglong; Zhang, Jichao; Li, Wei; Ren, Ning; Cui, Yunzhi; Zhang, Tao; Cai, Xiaoxiao; Li, Qian; et al.
Graphical abstract: Highlights: Blood exposure to graphene oxide (GO) causes anaphylactic death in primate animals. Long-circulation and distal lung deposition contribute to anaphylactic reaction. Anaphylactic reaction was manifested by elevated IgE level and severe lung injury. Case-by-case allergy tests are indispensable prior to the biomedical use of GO. Abstract: Toxicological evaluation of graphene oxide (GO) has been actively pursued under the context of large-scale industrial production and the potential for clinical translation. Nevertheless, the safety of GO remains largely debated, especially due to the lack of toxicological profile in higher mammals. Here we show that blood exposure to GO under the maximum safe starting dose may cause accidental death of mammals, including non-human primates (1 in 5 Macaca fascicularis and 7 in 121 mice), while remains general amenable in others. Elevated levels of immunoglobulin E and severe lung injury were found in dead animals, suggesting the GO-induced acute anaphylactic reactions. Noticeably, we did not observe anaphylactic reactions and deaths for two other carbon nanomaterials, including single-walled carbon nanotubes and nanodiamonds. This difference might arise from the long in-vivo circulating time of two-dimensional GO materials. This study thus highlights the urgent need to evaluate the hypersensitivity risks of graphene and other nanomaterials.